Performance of Optical Amplifiers With Regard To The Power Penalties of a DWDm Xgs-POnnetwork Environment - Marulanda Pungo, Ana María; Paredes Cerón, Paola Juliana; Gómez Agredo, Gustavo Adolfo (Ingeniería Solidaria, 2020)
Introduction:This article is the product of the research “Simulation level performance analysis of optical amplifiers for a DWDM XGS-PON network environment”, supported by the Research Group in New Technologies in Telecommunications (GNTT) of the University of Cauca during 2019. Problem:For the implementation of XGS-PON optical network architectures, amplification processes are required. These generate power penalties that lead to the presence of non-linear phenomena, significantly degrading network performance. Objective:To analyze the performance of a DWDM / XGS-PON network architecture, respecting the power penalties generated by implementing different types of optical amplifiers in different amplification modes. Methodology:Compilation of relevant bibliography on long-range network architectures with symmetric speeds of 10 Gbps. Results:Not working in the ideal region of amplification affects the performance of a DWDM XGS-PON network, generating a migration of a linear to non-linear propagation regime, due to the presence of power penalties such as FWM. Conclusion:With this investigation it is possible to determine which amplifier should be used according to the needs of the optical network, evaluating the different alternatives available in the market, depending on the cost, configuration and performance of the system. Originality:A new research is carried out for the performance of DWDM XGS-PON state-of-the-art network architectures, regarding the incidence of non-linear propagation phenomena. Restrictions:In some cases, the simulation tool requires a high consumption of machine resources and processing time.